PLAYBACK THEATER AS THE PRACTICE OF COMMUNITY-BASED SOCIAL HEALING - Fanahei, Rostyslav (Collection of scientific papers «ΛΌГOΣ», 2023)
Community-based social healing as a holistic approach involves healing of traumatized individual experiences through constant support of the communal environment, as well as the formation of harmonious interpersonal interaction through understanding and acceptance of the experiences of others. Playback Theater, with its ability to create a liminal space that mixes the individual and the collective dimensions in the specific experience of fused reality and imaginarity, is one the ways to achieve this goal. We are not talking about the exclusiveness of this method, but rather about concretizing a quite abstract adjustment of community-based social healing through an approach that is already developed at the practical and conceptual levels.